Implementasi Manajemen Berbasis Sekolah (MBS) Pada Madrasah Ibtidaiyah Al-Anwar Pangkalan Banteng Di Kabupaten Kotawaringin Barat - Wahyu Eka Fibrianto (FKIP, Universitas Palangka Raya, 2020)
This research aims to know: (1) the process of implementation school-based management in Madrasah Ibtidaiyah Al-Anwar Pangkalan Banteng Kabupaten Kotawaringin Barat, (2) the support and obstacle factors on the success of implementation school-based management in Madrasah Ibtidaiyah Al-Anwar Pangkalan Banteng. This research used Qualitative Research Method. The data collection technique was using observation, interview approach, documented all of the data needed (premier data). Then, it was analyzed qualitatively and the researcher took a conclusion. Results of the study (1) the teacher professionalism and their effort (2) the school cooperation, (3) the participation of stakeholders (the government, society, and the resident of school) (4) the openness of the school had run well, , (5) the improvement of school quality, Then, the support and obstacle factor that was often be faced in the success of school-based management in Madrasah Ibtidaiyah AlAnwar Pangkalan Banteng Kabupaten Kotawaringin Barat.